Cumplimiento tributario y la calidad de los servicios públicos de la Municipalidad Distrital de La Banda de Shilcayo 2025 - Paredes Lazo, Liz Jenny (2025)
The purpose of this final report was to determine the relationship between tax compliance and the quality of public services in the Banda de Shilcayo District Municipality, 2025. The study was conducted using a basic, descriptive correlational approach and a non-experimental design. The population consisted of 299 taxpayers from the district, who were administered a survey and a questionnaire as data collection instruments. The results reveal that tax compliance is fair, representing 25%. This is because taxpayers stated that they only occasionally know their tax obligations established by the municipality, and that they occasionally pay their municipal taxes on time. Regarding the quality of public services, this is also considered fair, at 25%. This is because, according to respondents, wastewater management facilities function properly only occasionally. Similarly, the municipality only occasionally implements effective measures to reduce violence and crime. Finally, a positive and statistically significant relationship was found between the variables, supported by a Spearman correlation coefficient of 0.705 and a bilateral significance level of less than 0.01. A high correlation was identified between tax compliance and service quality (r = 0.705; p < 0.01), as well as moderate relationships with tax commitment (r = 0.594; p < 0.01), tax burden (r = 0.591; p < 0.01), and attitude toward regulations (r = 0.640; p < 0.01).